CRITICAL LITERACY FOR DEMOCRATIC LEARNING IN CAREER EDUCATION - Hyslop‐Margison, Emery; Pinto, Laura (Canadian Journal of Education/Revue canadienne de l'éducation, 2007)
In this article, we explore the models of literacy conveyed by contemporary secondary career education policies, programs, and imperatives in the province of Ontario. The Ontario career education policies we reviewed uniformly advance a functional and socially reproductive model of literacy that undermines the democratic agency of learners. In response to these concerns, we propose that critical literacy should be introduced into Ontario secondary career education initiatives to encourage the democratic participation of students in shaping their vocational experience. Key words: false generosity, critical literacy, democratic learning Dans cet article, les auteurs analysent les modèles de littératie qui ressortent des politiques, programmes et impératifs actuels en matière de formation au choix d’une carrière au secondaire en Ontario. Les politiques ontariennes que les auteurs ont étudiées prônent toutes un modèle de littératie fonctionnel qui privilégie la reproduction sociale, modèle qui entrave l’action démocratique des apprenants. Tenant compte de cette préoccupation, les auteurs proposent l’introduction de la littératie critique dans les initiatives en matière de formation au choix de carrière en vue d’encourager les élèves à participer démocratiquement à leur orientation professionnelle. Mots clés : fausse générosité, littératie critique, apprentissage démocratique